2004
DOI: 10.1194/jlr.m300462-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and metabolism of leukotrienes in γ-glutamyl transpeptidase deficiency

Abstract: Leukotrienes (LTs) are active lipid mediators derived in the 5-lipoxygenase pathway. LTC 4 , the primary cysteinyl LT, is cleaved by ␥ -glutamyl transpeptidase (GGT), resulting in LTD 4 . We studied the synthesis and metabolism of LTs in three patients with GGT deficiency. LTs were analyzed in urine, plasma, and monocytes after HPLC separation by enzyme immunoassays, radioactivity detection, and electrospray tandem mass spectrometry. Analysis of LTs in urine revealed increased concentrations of LTC 4 (12.8-17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Other biochemical Wndings reported included increased plasma glutathione levels, low GGT activity, and the presence of -glutamylcysteine and cysteine in urine. Moreover, Mayatepek et al (2004) was able to measure leukotriene levels in monocytes, plasma and urine of three of these patients (the ones reported by Hammond et al and Wright et al) and found that they were completely deWcient in LTD4 synthesis. Phenotypically, patients varied in their symptoms.…”
Section: Human Ggt Dewciencymentioning
confidence: 99%
“…Other biochemical Wndings reported included increased plasma glutathione levels, low GGT activity, and the presence of -glutamylcysteine and cysteine in urine. Moreover, Mayatepek et al (2004) was able to measure leukotriene levels in monocytes, plasma and urine of three of these patients (the ones reported by Hammond et al and Wright et al) and found that they were completely deWcient in LTD4 synthesis. Phenotypically, patients varied in their symptoms.…”
Section: Human Ggt Dewciencymentioning
confidence: 99%
“…(79) Three of the patients show deficiencies in LTD 4 that are generated by a GGT-catalyzed reaction from the primary cysteinyl leukotriene LTC 4 . (80) …”
Section: Genes Involved In Glutathione Metabolismmentioning
confidence: 99%
“…[52] In addition to its gamma glutamyltranspeptidase activity it is also essential for leukotriene biosynthesis and bone metabolism as demonstrated in GGT deficient humans. [53] …”
Section: Serum Ggt and Oxidative Stress: Epidemiological Evidencementioning
confidence: 99%